Differentiated challenge-based learning: An innovative learning model for enhancing student scientific literacy - Paraniti, A.A.I.; Redhana, I.W.; Suma, K.; Suardana, I.N. (Edelweiss Applied Science and Technology, 2025)
Amidst the complexity of today’s global challenges, developing scientific literacy skills is crucial for fostering critical awareness and encouraging active community participation in responding to social and environmental issues. This study aims to determine the validity, practicality, and effectiveness of DCBL. It is a Research and Development (R&D) study that employs the ADDIE model to develop a Differentiated Challenge-Based Learning (DCBL) model. The study involved 1,589 high school students and 47 teachers in Bali during the needs analysis stage, 43 students and six teachers during the practicality test stage, and 381 11th-grade high school students during the effectiveness test stage. Data were collected through questionnaires and scientific literacy tests. Data analysis was conducted using descriptive analysis. The findings indicate that DCBL has been tested as valid with an Aiken’s V value of 0.953 and very practical with a score of 3.35. Although the ANOVA analysis results showed a significance value of 0.001 (p<0.005), the effect size is still relatively small (0.165). It was concluded that the DCBL learning model can be applied to improve scientific literacy skills. The research implications are that the application of the DCBL model provides a more adaptive and meaningful learning alternative. Through a combination of challenge-based and differentiated learning, teachers can accommodate the diversity of students’ abilities, interests, and learning styles, while fostering active engagement in understanding scientific concepts through real-life contexts.